Novel method for preparing cyclopentanone by catalytically converting biomass raw material through Cu-based non-noble metal catalyst

By using CuX/SBA-15 catalyst in a two-phase reaction system for sodium chloride aqueous solution/toluene, hemicellulose and xylose are converted into cyclopentanone in one step, solving the problems of environmental pollution, resource shortage and high production costs in the existing cyclopentanone production methods, and achieving efficient, environmentally friendly and high-purity cyclopentanone production.

CN119707651APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311275310.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing cyclopentanone production methods have problems such as difficult to deal with waste acid solutions, unfriendly environment, low product purity and high equipment costs, and relying on fossil energy to lead to environmental pollution and resource shortages.

Method used

CuX/SBA-15 catalyst (X = La, Ce, Y, Yb) was used to convert hemicellulose and xylose into cyclopentanone in one step under a two-phase reaction system of sodium chloride aqueous solution/toluene.

Benefits of technology

The high yield (up to 63%) and high purity of cyclopentanone is achieved, which avoids the problem of acid treatment and reduces production costs. Moreover, the process is acid-free and alkali-free, and the equipment is less corrosive, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for converting hemicellulose, xylan, xylose and arabinose in a primary biomass into cyclopentanone by using a novel CuX / SBA-15 (X = La, Ce, Y or Yb) catalyst. The system is a chlorate aqueous solution and methylbenzene two-item system, and hemicellulose, xylan, xylose and arabinose in the primary biomass can be prepared into high-yield cyclopentanone in one step under certain reaction conditions. The method has the advantages of mild reaction temperature, cheap catalyst, environment-friendly system and sustainable raw materials, and provides a novel method for preparing cyclopentanone from biomass raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing cyclopentanone by catalytic conversion of hemicellulose and xylose using a novel CuX / SBA-15 catalyst (X=La, Ce, Y, Yb). Specifically, the method is to use a CuX / SBA-15 catalyst (X=La, Ce, Y, Yb) sodium chloride aqueous solution / toluene organic solvent two-phase reaction system to directly convert hemicellulose and xylose and other reaction raw materials into cyclopentanone in one step under a hydrogen atmosphere. Background Art

[0002] Cyclopentanone is an important platform compound that can be used to prepare chemicals such as rubber, resin, coating and organic solvent. In addition, cyclopentanone is also widely used in the fields of drug synthesis and pesticide synthesis. Moreover, in life sciences, cyclopentanone is used as a neuroprotectant to reduce inflammation and cell death caused by central nervous system damage.

[0003] At present, there are several methods for industrial production of cyclopentanone. 1) Adipic acid method, i.e., using adipic acid as raw material, barium hydroxide as catalyst, and preparing cyclopentanone through decarboxylation and condensation reaction. The main problems of this method are that the waste acid solution is difficult to handle, the environment is extremely unfriendly, and the product purity is low. 2) Sodium hydroxide method, i.e., using cyclohexanone and sodium hydroxide as raw materials, preparing cyclopentanone under high temperature and high pressure conditions. This process needs to be carried out under high temperature and high pressure environment, and the equipment cost is high. It is worth noting that the raw materials of the above processes all come from fossil energy, and a large amount of greenhouse gases and other pollutants will be released during their mining, transportation and processing, which will cause air, water and soil pollution. Thereby affecting the ecological environment and human health. In addition, fossil energy reserves are limited, prices are unstable, and they are easily affected by political, economic and other factors. Therefore, there is also a certain uncertainty in over-reliance on fossil energy to prepare cyclopentanone. Biomass material is a renewable resource. Compared with fossil energy, it has better sustainability and environmental friendliness, so it can effectively alleviate the problems of fossil energy shortage and environmental pollution. Compared with fossil energy, biomass energy has a stable price and lower cost. The production cost can be reduced by catalytic conversion of biomass raw materials to prepare cyclopentanone. In summary, the relevant processes for catalytic conversion of biomass materials to prepare cyclopentanone have attracted widespread attention due to factors such as reduced production costs and reduced dependence on fossil energy.

[0004] At present, the commonly used raw material for preparing cyclopentanone from biomass is furfural. For example, in 2021, Hu and his colleagues in the field of cyclopentanone preparation research successively reported that Ni / SiO2 and Ni-P / Al2O3 catalysts showed high activity in the reaction of furfural to prepare cyclopentanone (Hongli Tian, ​​Xun Hu, etc. Molecular. Catal. 510 (2021) 111697; Guoming Gao, Xun Hu, etc. Catal. Sci. Technol. 11 (2021) 575.). In industry, furfural is obtained by treating biomass raw materials containing hemicellulose with sulfuric acid. The process itself has problems such as difficulty in handling acid liquid, which will cause certain adverse effects on the environment. In recent years, in order to better protect the environment and recycle catalysts to reduce costs, scientists have been committed to the solid acid catalytic conversion of hemicellulose to prepare furfural. In 2021, Zhang and his colleagues reported the use of SnO x In the work of converting xylose into furfural using a carbon-based catalyst, xylose was successfully converted into furfural at a reaction temperature of 180°C (Nan Zhou, Shicheng Zhang, etc. J. Cleaner. Production. 311 (2021) 127780, with a yield of 53.9%); Wang and his colleagues reported in 2021 that xylose was converted into cyclopentanone by carbon-supported solid acid catalysis (Hao Xu, Shurong Wang, etc. Energy Fuel 35 (2021) 9961), and the reaction temperature with better activity was 170 degrees Celsius, and a relatively considerable furfural yield (furfural yield was 84.9%) was obtained. Even so, in the process of converting hemicellulose or xylose to prepare furfural, the loss of heat energy and acid treatment are inevitable. Directly utilizing more primitive biomass raw materials such as xylose, xylan, or even raw biomass to convert and prepare cyclopentanone in one step can reduce the number of reaction steps and avoid the above-mentioned heat energy loss and waste acid problems to a certain extent, thereby improving energy utilization efficiency. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a new type of Cu-based catalyst, which can convert part of hemicellulose xylose into cyclopentanone in a sodium chloride aqueous solution and toluene system, with a yield of up to 63%. Compared with the prior art, the catalyst of this application is a pure non-precious metal catalyst and has a certain reaction stability. It is the first patent for the preparation of cyclopentanone by pure non-precious metals in this system. The process uses rare earth elements to modify copper-based catalysts, which makes the copper-based catalyst have better stability and activity. The reaction system is acid-free and alkali-free, and is not too corrosive to the reaction equipment, which is conducive to large-scale production. It is of great significance for the sustainable development of my country's energy, environmental protection, and the rapid realization of the strategic goals of carbon peak and carbon neutrality.

[0006] The following technical solutions are used to achieve this:

[0007] The present invention provides a method for preparing cyclopentanone by catalytic conversion of hemicellulose and xylose using a novel Cu-based catalyst:

[0008] Using CuX / SBA-15 (X=one or two of La, Ce, Y, Yb) as a catalyst, a sodium chloride aqueous solution / toluene two-phase reaction system, and a hydrogen atmosphere, the reaction raw material is directly converted into cyclopentanone in one step;

[0009] The reaction raw materials are hemicellulose components and monomers in biomass, including isomers of monomers, such as xylose, arabinose, or a mixture of two or more thereof.

[0010] Furthermore, in the above technical solution, the CuX / SBA-15 catalyst is a Cu-based catalyst with one or a mixture of La, Ce, Y, and Yb added as an additive, wherein the loading amount of Cu relative to the carrier SBA-15 is 10wt.% to 30wt.%, and the loading amount of the additive rare earth metal relative to the carrier is 1wt.% to 3wt.%.

[0011] Furthermore, in the above technical solution, the CuX / SBA-15 catalyst can be prepared by two methods:

[0012] Method 1: Prepare Cu / SBA-15 catalyst precursor by ammonia evaporation method, and then prepare CuLa / SBA-15, CuCe / SBA-15, CuY / SBA-15, and CuYb / SBA-15 catalyst precursor by impregnation method. After the prepared catalyst precursor is fully dried, it is burned in air; reduced under the condition of hydrogen and nitrogen mixture; passivated under the condition of air and nitrogen mixture, and finally prepare CuX / SBA-15 catalyst (X = one or two of La, Ce, Y, and Yb).

[0013] Method 2: Prepare CuX / SBA-15 catalyst precursor (X = one or two of La, Ce, Y, Yb) by co-impregnation method. After the prepared catalyst precursor is fully dried, it is calcined in air; reduced in a mixture of hydrogen and nitrogen; and passivated in a mixture of air and nitrogen to finally prepare CuX / SBA-15 catalyst (X = one or two of La, Ce, Y, Yb).

[0014] Furthermore, in the above technical scheme, in method 1, when the Cu / SBA-15 catalyst precursor is prepared by the ammonia evaporation method, a mixed raw material of Cu(NO3)2 3H2O and SBA-15 with a mass ratio of 0.38 to 1.14 is added to a round-bottom flask, and an appropriate amount of deionized water is added and stirred and mixed evenly, and then ammonia water is added to adjust the pH to 12 to 14, and then the round-bottom flask is placed in a water bath and stirred and heated at a heating temperature of 85 to 99°C until the pH reaches 6 to 8. After adjusting the pH, the product is filtered and washed, and placed in an oven to dry. After being completely dried, the product is taken out, and a nitrate aqueous solution of appropriate concentration (X(NO3); X = one or two of La, Ce, Y, and Yb) is added, and the mixture is evenly stirred and dried. The mixture is then calcined in an air atmosphere at a calcination temperature of 400 to 800° C. The calcined sample is reduced in a hydrogen and nitrogen mixed atmosphere at 300 to 800° C. The reduced sample is passivated in an air and nitrogen mixed atmosphere for 24 hours to obtain a CuX / SBA-15 catalyst (X = one or two of La, Ce, Y, and Yb).

[0015] Furthermore, in the above technical scheme, in method 2, the CuX / SBA-15 catalyst is prepared by co-impregnation method, after adding a certain amount of SBA-15 into the container, Cu(NO3)2 3H2O and nitrate aqueous solution (X(NO3); X = one or two of La, Ce, Y, Yb) are added, wherein the loading amount of Cu relative to the carrier is 10wt.%~30wt.%, and the loading amount of rare earth metal relative to the carrier is 1wt.%~3wt.%, and the product is placed in an oven for drying after stirring evenly. The dried precursor is calcined in an air atmosphere at a calcination temperature of 400~800°C, and the burned sample is reduced in a hydrogen and nitrogen mixed atmosphere at 300~800°C, and finally passivated in an air and nitrogen mixed atmosphere for 24 hours to obtain the CuX / SBA-15 catalyst.

[0016] Furthermore, in the above technical solution, in the sodium chloride aqueous solution / toluene two-phase reaction system, the concentration of the sodium chloride aqueous solution is 2wt.% to 15wt.%, and under the hydrogen atmosphere, the hydrogen pressure is 2 to 8Mpa, and the reaction temperature is 140 to 240°C. DETAILED DESCRIPTION

[0017] Examples 1 to 3

[0018] Take a 100mL round-bottom flask, add 1g SBA-15 and 0.38g, 0.76g, and 1.14g Cu(NO3)2 3H2O respectively, then add 20mL of deionized water to the round-bottom flask, fix the round-bottom flask in the oil bath with an iron stand, turn on the stirring, and slowly add ammonia water to adjust the pH to 12-14. Heat the oil bath to 90℃ until the pH is 6-8. Stop heating and stirring, take out the sample, filter and wash it, place it in an oven to dry, and record it as Cu 10 / SBA-15、Cu 20 / SBA-15、Cu 30 / SBA-15. The dried Cu 10 / SBA-15、Cu 20 / SBA-15、Cu 30 / SBA-15 were loaded into beakers respectively, and appropriate amounts of La(NO3)3 solution were added to the three beakers respectively, so that the loading amount of metal La on the catalyst was 3wt.%. Then an appropriate amount of water was added to the beaker and stirred evenly. After the equal amount of impregnation is completed, the catalyst is placed in a cool and windless place for 24 hours, and then placed in an oven for drying. The prepared precursor was placed in a muffle furnace, and then calcined at 400°C for 4 hours in an air atmosphere. The calcined sample was then placed in a tubular furnace and reduced at 500°C for 4 hours under a mixture of hydrogen and nitrogen. After the reduction is completed and the tubular furnace is cooled to room temperature, the sample is passivated for 24 hours under a mixture of nitrogen and air. The samples were named Cu 10 La / SBA-15、Cu 20 La / SBA-15、Cu 30 La / SBA-15.

[0019] Cu 10 La / SBA-15、Cu 20 La / SBA-15、Cu 30 La / SBA-15 was used for xylose conversion experiments. 0.3g xylose, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. Hydrogen gas of 3Mpa was injected into the reactor, and the reactor was reacted at 160℃ and 500rpm for 4 hours. The reaction results are shown below.

[0020] Table 1. Conversion of xylose to cyclopentanone using different catalysts [a]

[0021]

[0022] [a] Reaction conditions: 160°C, 500 rpm, 4 hours

[0023] As shown in Table 1, in the CuLa / SBA-15 catalyst, different Cu loadings have a certain effect on the reaction. The results show that 10wt.% copper loading has the best selectivity and yield for cyclopentanone. When the copper loading in the CuLa / SBA-15 catalyst is 20wt.% or 30wt.%, although the cyclopentanone yield is acceptable, it is still lower than that of CuLa / SBA-15. 10 La / SBA-15 has decreased. This is because the conversion of xylose to prepare cyclopentanone is a reaction that integrates multiple reaction routes. Xylose is first isomerized to xylulose in a NaCl aqueous solution, and xylulose is dehydrated to form furfural, which is then hydrogenated to form furfural alcohol. After xylose is converted to furfural alcohol, the reaction route will be divided into the following three: 1) Furfuryl alcohol is isomerized to form hydroxycyclopentenone, which is dehydrated and hydrogenated to form cyclopentanone, and then cyclopentanone can be further hydrogenated to form cyclopentanol; 2) Furfuryl alcohol is further hydrogenated to form tetrahydrofurfuryl alcohol; 3) Furfuryl alcohol is hydrogenated and dechlorinated to form methylfuran, and then methylfuran is further hydrogenated to form methyltetrahydrofurfuryl alcohol. It is worth noting that methyltetrahydrofurfuryl alcohol can also be produced by the hydrogenation and dechlorination of tetrahydrofurfuryl alcohol. The above reaction routes are as follows:

[0024]

[0025] As the amount of Cu increases, the following side reactions become more intense: 1) Over-hydrogenation of furfuryl alcohol to produce tetrahydrofurfuryl alcohol; 2) Hydrogenation and dechlorination of furfuryl alcohol to produce methyl furan; 3) Over-hydrogenation of cyclopentanone to produce cyclopentanol. Therefore, too much Cu will lead to a decrease in the yield of cyclopentanone. When the Cu loading is 10wt.%, the yield of cyclopentanone is the highest, reaching 64%.

[0026] Embodiments 4 to 6

[0027] Take 1g of SBA-15 and add it to a beaker; then add 0.38g, 0.76g, and 1.14g of Cu(NO3)23H2O and an appropriate amount of La(NO3)3 solution to three beakers respectively. Add a certain amount of water to mix the two salts into a uniform solution, and then pour them into the beakers containing SBA-15 for equal immersion. Make the loading amount of metal La on the catalyst 3wt.%. Place the sample in a cool and windless place for 24 hours, and then put it in an oven to dry. After the sample is dried, it is calcined at 400℃ in an air atmosphere for 4 hours, and then placed in a tubular furnace and reduced at 500℃ for 4 hours in a mixture of hydrogen and nitrogen. After the reduction is completed and the tubular furnace is cooled to room temperature, the sample is passivated in a mixture of nitrogen and air for 24 hours. The samples are named 2-Cu 10 La / SBA-15, 2-Cu 20 La / SBA-15, 2-Cu 30 La / SBA-15.

[0028] With 2-Cu10 La / SBA-15, 2-Cu 20 La / SBA-15, 2-Cu 30 La / SBA-15 was used for xylose conversion experiments. 0.3g xylose, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. Hydrogen gas of 3Mpa was injected into the reactor, and the reactor was reacted at 160℃ and 500rpm for 4 hours. The reaction results are shown below.

[0029] Table 2. Conversion of xylose to cyclopentanone using different catalysts [a]

[0030]

[0031]

[0032] [a] Reaction conditions: 160°C, 500 rpm, 4 hours.

[0033] As shown in Table 2, 2-Cu 10 The yield and selectivity of cyclopentanone of La / SBA-15 catalyst, as well as the reaction phenomenon, are similar to those of the catalyst prepared by first distilling ammonia and then impregnating. The yield of cyclopentanone can reach up to 63%.

[0034] Embodiments 7 to 10

[0035] Take 1g of SBA-15 and add it to a beaker; then add 0.38g of Cu(NO3)2 3H2O and an appropriate amount of La(NO3)3 solution to three beakers respectively. Add a certain amount of water to mix the two salts into a uniform solution, and then pour them into the beakers containing SBA-15 for equal immersion. The loading amount of metal La on the catalyst is 3wt.%. Place the sample in a cool and windless place for 24 hours, and then put it in an oven to dry. After the sample is dried, it is calcined at 300, 400, 600, and 800℃ in an air atmosphere for 4 hours, and then placed in a tubular furnace and reduced at 500℃ for 4 hours in a mixture of hydrogen and nitrogen. After the reduction is completed and the tubular furnace is cooled to room temperature, the sample is passivated in a mixture of nitrogen and air for 24 hours. The samples were named 300-Cu 10 La / SBA-15, 400-Cu 10 La / SBA-15, 600-Cu 10 La / SBA-15, 800-Cu 10 La / SBA-15.

[0036] 300-Cu 10 La / SBA-15, 400-Cu10 La / SBA-15, 600-Cu 10 La / SBA-15, 800-Cu 10 La / SBA-15 was used for xylose conversion experiments. 0.3g xylose, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. Hydrogen gas of 3Mpa was injected into the reactor, and the reactor was reacted at 160℃ and 500rpm for 4 hours. The reaction results are shown in the following table.

[0037] Table 3. Conversion of xylose to cyclopentanone using different catalysts [a]

[0038]

[0039] [a] Reaction conditions: 160°C, 500 rpm, 4 hours.

[0040] As shown in Table 3, the performance of the catalysts prepared at different calcination temperatures is somewhat different. Too high a calcination temperature is not conducive to the hydrogenation activity of the catalyst.

[0041] Examples 11 to 18

[0042] Cu 10 La / SBA-15 was used for xylose conversion experiment. 0.3g xylose, 30mg catalyst and NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. Hydrogen gas of 3Mpa was injected into the reactor, and the reactor was reacted at 160℃ and 500rpm for 4 hours. The reaction results are shown in the following table.

[0043] Table 4. Cu 10 La / SBA-15 catalyst catalyzes conversion of xylose to cyclopentanone in sodium chloride solutions with different concentrations [a]

[0044]

[0045] [a] Reaction conditions: 160°C, 500 rpm, 4 hours.

[0046] As shown in Table 4, the change in NaCl concentration significantly affects the product distribution of the reaction. When there is no sodium chloride in the reaction system, the catalyst is not poisoned and exhibits a strong hydrogenation performance. It is well known that Cu is a commonly used metal active component for the hydrogenation of sugars to prepare sugar alcohols. Therefore, xylose is used as a reaction substrate and is all hydrogenated to xylitol. When the concentration of the NaCl aqueous solution is 2wt.%, cyclopentanone begins to be generated, but the yield is not considerable, and tetrahydrofurfuryl alcohol appears as the main by-product. The reason is that the hydrogenation activity of the catalyst is too strong, and the reaction intermediate furfuryl alcohol is transitionally hydrogenated to tetrahydrofurfuryl alcohol. It is worth noting that although the catalyst exhibits excessive hydrogenation performance, the by-product is not xylitol, which shows that the addition of sodium chloride can well promote the isomerization reaction of xylose, converting it into xylulose, and then further dehydrating and hydrogenating it into furfuryl alcohol. As the NaCl concentration continues to increase, it can be clearly seen that the hydrogenation performance of the catalyst is gradually weakening. When the NaCl concentration reaches 20wt.%, the hydrogenation activity of the catalyst is completely lost, so the only reaction product is furfural converted from xylose through isomerization and dehydration.

[0047] Examples 19 to 25

[0048] Cu 10 La / SBA-15 was used for xylose conversion experiment. 0.3g xylose, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. Hydrogen was flushed into the reactor and reacted at 160℃ and 500rpm for 4 hours. The reaction results are shown in the following table.

[0049] Table 5. Cu 10 La / SBA-15 catalyst catalyzes conversion of xylose to cyclopentanone in sodium chloride solutions with different concentrations [a]

[0050]

[0051] Reaction conditions: 160°C, 500 rpm, for 4 hours.

[0052] As shown in Table 5, when the pressure of hydrogen is too small, the furfural converted from xylose isomerization dehydration cannot be fully hydrogenated to furfuryl alcohol, so the cyclopentanone yield is not optimistic under the reaction conditions with low hydrogen pressure. Along with the increase of hydrogen pressure, hydrogenation reaction intensifies, and furfural is fully converted into furfuryl alcohol and then further converted into cyclopentanone. When hydrogen pressure is 3MPa, the yield of cyclopentanone is the highest. But when hydrogen pressure is too high, the reaction of furfuryl alcohol hydrodechlorination generating methylfuran and the reaction of furfuryl alcohol overhydrogenation generating tetrahydrofurfuryl alcohol intensify, causing the yield of cyclopentanone to decrease.

[0053] Examples 26-31

[0054] Cu 10 La / SBA-15 was used for xylose conversion experiment. 0.3g xylose, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. 2MPa hydrogen was injected into the reactor and the reaction was carried out at 500rpm for 4 hours. The reaction results are shown in the following table.

[0055] Table 6. Cu 10 La / SBA-15 catalyst catalyzes conversion of xylose to cyclopentanone in sodium chloride solutions with different concentrations [a]

[0056]

[0057]

[0058] Reaction conditions: 500 rpm for 4 hours

[0059] As shown in Table 6, the reaction temperature has a certain influence on the reaction. When the temperature is low, the factors affecting the formation of cyclopentanone are as follows: 1) xylose is difficult to be converted into furfural through isomerization and dehydration reaction; 2) furfuryl alcohol is difficult to isomerize into cyclic ketone. When the reaction temperature is too high, although the type of product does not change much, the carbon balance of the reaction becomes very poor. This may be because at high temperature, furfural, furfuryl alcohol and cyclopentanone will undergo polymerization reaction to generate larger molecular compounds, which are difficult to detect in gas chromatography.

[0060] Examples 32-34

[0061] Cu 10 La / SBA-15 was used for the conversion experiment of different reaction substrates. 0.3g reaction substrate, 30mg catalyst, and 0.6g NaCl were added to a 100mL reactor, and then 20mL deionized water and 10mL toluene were added to the reactor. 2MPa hydrogen was injected into the reactor and the reaction was carried out at 500rpm for 4 hours. The reaction results are shown in the following table.

[0062] Table 3. Preparation of cyclopentanone from different reaction substrates [a]

[0063]

[0064] [a] Reaction conditions: 160°C, 500 rpm, 4 hours.

[0065] Examples 35-38

[0066] The xylose conversion experiment was carried out using different catalysts. 0.3g of reaction substrate, 30mg of catalyst, and 0.6g of NaCl were added to a 100mL reactor, and then 20mL of deionized water and 10mL of toluene were added to the reactor. 2MPa of hydrogen was flushed into the reactor and the reaction was carried out at 500rpm for 4 hours. The reaction results are shown in the following table.

[0067] Table 3. Preparation of cyclopentanone by different catalysts [a]

[0068]

[0069]

[0070] [a] Reaction conditions: 160°C, 500 rpm, 4 hours.

Claims

1. A method for preparing cyclopentanone by catalytic conversion of hemicellulose and xylose using a novel Cu-based catalyst, characterized in that: Using CuX / SBA-15 as a catalyst and a sodium chloride aqueous solution / toluene two-phase reaction system, the reaction raw material is directly converted into cyclopentanone in one step under a hydrogen atmosphere; wherein X is selected from one or two of La, Ce, Y, and Yb; The reaction raw materials are hemicellulose components and monomers in biomass, and also include isomers of the monomers.

2. The method according to claim 1, characterized in that: The CuX / SBA-15 catalyst is prepared by adding one or a mixture of two or more of La, Ce, Y and Yb to a Cu-based catalyst as an additive; wherein the loading amount of Cu relative to the carrier SBA-15 is 10wt.% to 30wt.%, and the loading amount of the additive rare earth metal relative to the carrier is 1wt.% to 3wt.%.

3. The method according to claim 1, characterized in that: The CuX / SBA-15 catalyst can be prepared by two methods: Method 1: Prepare Cu / SBA-15 catalyst precursor by ammonia evaporation method, and then prepare CuX / SBA-15 catalyst precursor by impregnation method; After the prepared catalyst precursor is fully dried, it is burned in air; it is reduced in a mixture of hydrogen and nitrogen; it is passivated in a mixture of air and nitrogen, and finally a CuX / SBA-15 catalyst is prepared; Method 2: Preparation of CuX / SBA-15 catalyst precursor using co-impregnation method; After the prepared catalyst precursor is fully dried, it is calcined in air; reduced in a hydrogen and nitrogen mixed gas condition; and passivated in an air and nitrogen mixed gas condition, and finally a CuX / SBA-15 catalyst is prepared.

4. The method according to claim 3, characterized in that: Method 1 is specifically as follows: Cu(NO3)2 3H2O and SBA-15 are mixed in a mass ratio of 0.38 to 1.14, and an appropriate amount of deionized water is added to stir and mix evenly, and then ammonia water is added to adjust the pH to 12 to 14, and the mixture is stirred and heated at a temperature of 85 to 99°C until the pH reaches 6 to 8; after the pH is adjusted, the product is filtered and washed, and placed in an oven for drying. After it is completely dried, the product is taken out and an appropriate concentration of nitrate aqueous solution X(NO3) is added; X is selected from one or two of La, Ce, Y, and Yb, and the mixture is dried after uniform stirring, and then calcined in an air atmosphere at a calcination temperature of 400 to 800°C. The calcined sample is reduced in a hydrogen and nitrogen mixed atmosphere at 300 to 800°C, and the reduced sample is passivated in an air and nitrogen mixed atmosphere for 24 hours to obtain a CuX / SBA-15 catalyst.

5. The method according to claim 3, characterized in that: Method 2 is specifically as follows: after adding a certain amount of SBA-15 into a container, Cu(NO3)2 3H2O and a nitrate aqueous solution X(NO3) are added; X is selected from one or two of La, Ce, Y, and Yb. After stirring evenly, the product is placed in an oven to dry. The dried precursor is calcined in an air atmosphere at a calcination temperature of 400 to 800°C. The burned sample is reduced in a hydrogen and nitrogen mixed atmosphere at 300 to 800°C, and finally passivated in an air and nitrogen mixed atmosphere for 24 hours to obtain a CuX / SBA-15 catalyst.

6. The method according to claim 1, characterized in that: In the sodium chloride aqueous solution / toluene two-phase reaction system, the concentration of the sodium chloride aqueous solution is 2wt.% to 15wt.%, and under the hydrogen atmosphere, the hydrogen pressure is 2 to 8Mpa, and the reaction temperature is 140 to 240°C.

7. The method according to claim 1, characterized in that: The isomer of the monomer is selected from xylose, arabinose or a mixture of the two.